The scents of Marie-Claire - Sālimī, al-Ḥabīb (Modern Arabic literature., 2010)
This novel from one of Tunisiaʹs leading writers, the first of his works to be translated into English, narrates a love story in all its stages, in all its glorious and inglorious details. Moment by moment we become acquainted with the morning rituals, the desires of the flesh, the turbulence of the spirit, and even a few unattractive personal habits. It is a journey that takes us inside the nuances of what passes between two lovers, from the first glances of attraction to the final words of anger. It is a journey filled with all the hallmarks of the complex relationship between one man and one woman -- the mystery and the ambiguity, the intricacy and the confusion -- which, in the end, serve to expose its fragility. This is an intimate tale that manages to tell not only the story of two individuals, but also that of the collision of two cultures. -- Jacket.